1994
DOI: 10.1128/aac.38.8.1849
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ofloxacin and its metabolites in cerebrospinal fluid after a single intravenous infusion of 400 milligrams of ofloxacin

Abstract: Ofloxacin has been reported to diffuse readily into the cerebrospinal fluid (CSF) in subjects with both inflamed and uninflamed meninges. However, with moderately susceptible bacteria, ofloxacin concentrations in CSF may be subtherapeutic after administration of an intravenous (i.v.) dose of 200 mg. For this reason, the kinetics of a higher dose of ofloxacin in CSF was studied with humans. Six patients with occlusive hydrocephalus caused by cerebrovascular diseases who had undergone external ventriculostomy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The lack of a positive relationship between the CSF/plasma rufloxacin concentration ratio and indices of meningeal permeability in patients with purulent meningitis supports the observation that rufloxacin enters the CSF even in the presence of a normal blood-CSF barrier. Similar results have previously been obtained with ofloxacin (19) and rifampin (17). Passage of lipophilic antibacterial agents across capillary epithelial cells of the blood-CSF barrier is less dependent on the derangement of the barrier than is the transit of hydrophilic compounds (2).…”
Section: Discussionsupporting
confidence: 75%
“…The lack of a positive relationship between the CSF/plasma rufloxacin concentration ratio and indices of meningeal permeability in patients with purulent meningitis supports the observation that rufloxacin enters the CSF even in the presence of a normal blood-CSF barrier. Similar results have previously been obtained with ofloxacin (19) and rifampin (17). Passage of lipophilic antibacterial agents across capillary epithelial cells of the blood-CSF barrier is less dependent on the derangement of the barrier than is the transit of hydrophilic compounds (2).…”
Section: Discussionsupporting
confidence: 75%
“…i.v., the CSF to plasma C max ss ratio 2 h after dosing averaged 35%, ranging between 23 and 42%. Finally, in six patients with external ventriculostomy, Nau and coworkers (20) demonstrated that after administration of a single 400-mg dose, the level of CSF penetration of ofloxacin, namely, the racemate of l-and d-ofloxacin, enabled an average CSF-toserum-AUC ratio of 0.65 (range, 0.59 to 0.81) and a mean peak level in CSF of 2.04 mg/liter to be achieved 1.75 h after dosing. The persistence in the ventricular CSF of effective concentrations that lasted for the entire dosing interval suggested that optimal exposure to levofloxacin may be achieved in all parts of the CSF system, considering that, in general, antibiotic concentrations were found to be severalfold lower at the ventricular CSF level than at the lumbar CSF level (21).…”
Section: Discussionmentioning
confidence: 99%
“…They probably cannot be applied to lumbar drug concentrations: The protein concentration gradient from ventricular to lumbar CSF, which also applies to radiolabeled albumin administered IV [17] suggests that, after IV administration antibiotic concentrations found in lumbar CSF may be higher than those in ventricular CSE In fully developed bacterial meningitis, CSF concentrations of hydrophilic drugs were higher than those estimated by us. With lipophilic antibacterials, the CSF concentrations are less influenced by the state of the blood-CSF barrier [5,10,13].…”
Section: Discussionmentioning
confidence: 99%